Clinical and Immunological Phenotypes of Alopecia Areata in Children with Concomitant Atopic Dermatitis: Results of a Cluster Analysis - N.N. Potekayev; G.P. Tereshchenko; A.G. Gadzhigoroeva; A.L. Savastenko; M. Kurdi; O.V. Zhukova (Russian Journal of Clinical Dermatology and Venereology, 2026)
Background. Alopecia areata (AA) and atopic dermatitis (AD) are chronic immune-mediated diseases that frequently coexist in children. Despite established epidemiological links, the internal structure of this comorbidity, including how objective disease severity and polyatopy correlate, remains poorly characterized. Aim. To identify and characterize clinical-immunological phenotypes of AA in children with concomitant AD using cluster analysis. Methods. A single-center, cross-sectional study included 68 children aged 5—16 years with AA and AD. Assessments included disease severity (SALT, SCORAD), age of AA onset, serum total IgE, quality of life (CDLQI), and atopic comorbidity (Atopy Index: 0=AD only, 1=+1 atopic condition, 2=+≥2 conditions). Spearman’s correlation and k-means clustering (variables: SALT, SCORAD, IgE, age of AA onset) were used. Results. Correlation analysis revealed a moderate positive association between AA and AD severity (ρ=+0.512, p